A review of salivary gland histopathology in primary Sjögren's syndrome with a focus on its potential as a clinical trials biomarker. Issue 9 (1st June 2015) - Fisher, Benjamin A; Brown, Rachel M; Bowman, Simon J; Barone, Francesca
Abstract : Salivary gland changes, characterised by a focal lymphocytic sialadenitits, play an important role in the diagnosis of primary Sjögren's syndrome (PSS) and were first described over 40 years ago. Recent evidence suggests that minor salivary gland biopsy may also provide information useful for prognostication and stratification, yet difficulties may arise in the histopathological interpretation and scoring, and evidence exists that reporting is variable. With the increasing number of actual and proposed clinical trials in PSS, we review the evidence that might support the role of histopathology as a biomarker for stratification and response to therapy and highlight areas where further validation work is required.